Releitura eliasiana de Sérgio Buarque de Holanda: democracia e personalismo no Brasil contemporâneo - Ferreira, Gabriela de Resende [UNESP] (2014)
This is a critical reflection of the current models of reading about democracy in Brazil, from an articulation between Norbert Elias´s theory of social processes and Sérgio Buarque de Holanda´s concept of personalism. Therefore, this research uses the sociological theory of processes in Norbert Elias as a bridge between contemporary social theory and the area of social thought in Brazil. Thus, instead of personalism like singular cultural trait, becomes a concept rethought as a pattern of emotion, thought and action, that is taken from a social and collective fund of knowledge, and that belongs to Brazilian reality. This retelling of Sérgio Buarque de Holanda by Norbert Elias offers to the current approaches to democratization in Brazil a sociological model focused on investigating how long-term changes in both social and personality structure, promotes specific processes of democratization.